Evaluasi Penggunaan Obat Pada Pasien Gagal Ginjal Kronik Di Rumah Sakit Umum Daerah Sanjiwani Gianyar - Dewi Puspita Apsari; Putu Eka Arimbawa; Ni Luh Manik Rahayuni (Bali International Scientific Forum, 2022)
Abstract Baground: Chronic kidney failure is kidney damage that causes the kidneys to be unable to get rid of toxins and waste blood products in the kidneys, marked by the presence of protein in the urine and a decrease in the glomerular filtration rate (GFR) which lasts for approximately three months. Management of chronic kidney failure is most often done with hemodialysis. Purpose: This study aims to evaluate the use of drugs in patients with chronic kidney failure undergoing hemodialysis at the Sanjiwani Hospital. Method: The method in this research is descriptive with purposive sampling technique. The number of samples was 55 medical records of patients with chronic kidney failure undergoing hemodialysis at the Sanjiwani Hospital, Gianyar in 2021. Data processing used Microsoft Excel and analyzed descriptively comparing the results with the guidelines. Results: The results showed that most of the drug use used antihypertensive, antianemic, vitamin and mineral therapy classes. Evaluation of drug use in patients with chronic kidney failure undergoing hemodialysis based on 4 criteria, namely the right patient (100%), the right indication (100%), the right drug (92.73%) and the right dose (69.09). Conclusion: The rationale for the use of drugs is categorized as having met the criteria for the right patient and the right indication, while for the criteria for the right drug and the right dose there is still the use of drugs and inappropriate doses. Keywords: Chronic Renal Failure, Evaluation of Drug Use, Rationality